Imaginary axis as a basic morphology in the city of Yogyakarta - Indonesia - Karsono, Bambang; Wahid, Julaihi (2008)
The life and characteristic of the cities in Indonesia cannot be separated by the influence of city’s development in Java Island. The influenced of Javanese cultures not only in the cultural system, governmental mechanism or political behavior of the administration, but also on the dimensions of the established institutions; it starts from the beginning of the Mataram Hindu Empire, the Majapahit Empire as well as the Mataram Islamic influence of the recent time. In this paper the term “axis” as a basis of morphology for creating city’s order in a traditional city of Indonesia especially in Java is analyzed. Here it is applied in the order of ancient city of Trowulan Majapahit. This axis was influenced by the growth of religions as a cosmology orientation. Certain imaginary axis which acts as a joint connects the various cosmic forces of the universe. Besides in the city development plan, this imaginary axis is applied as a “road system”. An axis of the sun orbit is the easiest cosmic force we can feel in everyday life. Thus, the shapes of the traditional cities in Java and on the island of Bali tend to incline on the order East - West axis or North-South axis. Orientation of the buildings has been developed according to such orientation too. Meanwhile giving honor to the universal objects as the cosmic forces such as mountains, rivers, lakes and sea, have been applied in the city planning. This paper also delves into the concept of imaginary axis influenced by the shaping of elements of the traditional city in Indonesia, especially the placement of alun-alun, keraton and the mosque. Philosophically, Yogyakarta has been shaped by cosmology axis which cannot be inseparable from those elements such as Merapi Mountain, Keraton and Southern Sea (Indian Ocean). This order referred to Trowulan Majapahit space and order which is known as a concept of space according to Hinduism.